1998
DOI: 10.1096/fasebj.12.3.341
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of myosin light‐chain kinase in the regulation of agonist‐ and fluid flow‐stimulated Ca2+influx in endothelial cells

Abstract: Cytosolic Ca2+ ([Ca2+]i) plays an important role in endothelial cell signaling. Although it has been suggested that the influx of Ca2+ can be triggered by depletion of intracellular Ca2+ stores, the mechanism (or mechanisms) underlying this phenomenon needs further elaboration. In the present study, involvement of myosin light-chain kinase (MLCK) in the regulation of Ca2+ signaling was investigated in agonist- and fluid flow-stimulated endothelial cells loaded with Ca2+-sensitive dyes. Bradykinin (BK) and thap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 35 publications
5
55
1
Order By: Relevance
“…There is ample evidence suggesting that MLCK phosphorylation of MLC is a critical signaling event associated with intracellular Ca 2+ in actin-based cytoskeletal remodeling. It has recently been shown that ML-9, an inhibitor of MLCK, abolishes MLC phosphorylation and Ca 2+ influx in porcine aortic ECs in response to shear stress (57). Thus, shear stress is likely to activate the Rhop160ROCK pathway, which in turn modulates the MLCK-MLC pathway or the intracellular Ca 2+ to regulate the cell alignment and stress fiber formation.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence suggesting that MLCK phosphorylation of MLC is a critical signaling event associated with intracellular Ca 2+ in actin-based cytoskeletal remodeling. It has recently been shown that ML-9, an inhibitor of MLCK, abolishes MLC phosphorylation and Ca 2+ influx in porcine aortic ECs in response to shear stress (57). Thus, shear stress is likely to activate the Rhop160ROCK pathway, which in turn modulates the MLCK-MLC pathway or the intracellular Ca 2+ to regulate the cell alignment and stress fiber formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, release of Ca 2 + from stores appears to stimulates influx of Ca 2 + across the plasma membrane, a process termed capacitative calcium entry (CCE) (Putney et al, 2001). The mechanism of action of CCE is unclear and a variety of explanations have been suggested, including: direct regulation of Ca 2 + channels in the plasma membrane by Ca 2 + concentration in the cytosol; release-sensitive production of a diffusible "calcium influx factor"; activation of Ca 2 + channels by kinases (such as tyrosine kinase and myosin light chain kinase), produced as a result of Ca 2 +-calmodulin complexes in the cytosol; conformational coupling between the IP 3 sensitive channel in the ER and Ca 2 + channels in the plasma membrane (Watanabe et al, 1998;Tran et al, 2000;Putney et al, 2001). CCE appears to be inhibited by cyclic guanosine monophosphate (cGMP) and G-kinase, which are produced as downstream effects of NO and Ca 2 + signalling.…”
Section: Model For Endothelial Calcium Dynamicsmentioning
confidence: 99%
“…CaM kinase II is a multifunctional enzyme that is required for both granule mobilization under stimulating conditions and maintenance of secretory capacity under resting conditions in pancreatic β cells (48). MLCK regulates capacitative Ca 2+ entry (49) and is involved in Ca 2+ -dependent secretion of insulin (50) and rennin (51). NO increases cGMP formation through the stimulation of soluble guanylate cyclase (GC-s) (52,53).…”
Section: Intracellular Signals For the Translocation Of Aqp5 Towards mentioning
confidence: 99%